RANCANGAN DAN IMPLEMENTASI SISTEM PERPUSTAKAAN CERDAS BERBASIS SMART CARD DENGAN TEKNOLOGI NEAR FIELD COMMUNICATION (NFC) PADA POLITEKNIK PENERBANGAN MEDAN - Erwin Lumban Gaol; Mochammad Zen Samsono Hadi; Aries Pratiarso (Jurnal Nasional Teknologi Komputer, 2025)
In today's digital era, efficient and modern library management has become an essential need for educational institutions. Medan Aviation Polytechnic as one of the institutions under the Ministry of Transportation, requires a library system that can optimize the borrowing and returning processes, as well as enhance services to users. This study aims to design and implement a smart library system based on smart card technology using Near Field Communication (NFC). The developed system utilizes smart cards as library membership cards integrated with NFC technology to facilitate access to the library system. The research methodology includes literature review, system design, implementation, and system testing. The test results show that all smart cards were successfully detected by the system, and only registered cards were allowed access. The maximum reading distance of the NFC reader was 4 cm, with an average access time of 0.42 seconds. The system also accurately classified book borrowing based on study programs. All system features functioned properly and received a high level of user satisfaction, with an average score of 4.59 out of 5, indicating that the system meets user needs, improves service quality, and modernizes library management.